2000
DOI: 10.1109/4233.826861
|View full text |Cite
|
Sign up to set email alerts
|

Laryngeal pathology detection by means of class-specific neural maps

Abstract: Most of the existing systems and methods for laryngeal pathology detection are characterized by a classification error. One of the basic problems is the approximation and estimation of the probability density functions of the given classes. In order to increase the accuracy of laryngeal pathology detection and to eliminate the most dangerous error--classification of a patient with laryngeal disease as a normal speaker--here an approach based on modeling of the probability density functions (pdf's) of the input… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(22 citation statements)
references
References 13 publications
1
20
0
1
Order By: Relevance
“…Description x 1 Pitch x 2 Jitter x [3][4][5] 3 different estimations of shimmer x [6][7] parameters related with glottal closure x [8][9][10] 3 parameters related with HNR x [11][12][13][14] MWC power spectral density in 4 bins x [15][16][17][18][19][20][21][22][23] Amplitude of the MWC PSD singularities as described in (14) x [24][25][26][27][28][29][30][31][32] Position of the MWC PSD singularities as described in (14) x [33][34] Slenderness of the first and second "V" notches as described in (14) x [35][36][37] Estimations of the vocal fold body biomechanical parameters as described in (15) x [38][39][40] Estimations of the vocal fold cover biomechanical parameters as described in (15) x [41][42][43] Vocal fold body biomechanical parameter unbalance as described in (15) x [44][45]<...>…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Description x 1 Pitch x 2 Jitter x [3][4][5] 3 different estimations of shimmer x [6][7] parameters related with glottal closure x [8][9][10] 3 parameters related with HNR x [11][12][13][14] MWC power spectral density in 4 bins x [15][16][17][18][19][20][21][22][23] Amplitude of the MWC PSD singularities as described in (14) x [24][25][26][27][28][29][30][31][32] Position of the MWC PSD singularities as described in (14) x [33][34] Slenderness of the first and second "V" notches as described in (14) x [35][36][37] Estimations of the vocal fold body biomechanical parameters as described in (15) x [38][39][40] Estimations of the vocal fold cover biomechanical parameters as described in (15) x [41][42][43] Vocal fold body biomechanical parameter unbalance as described in (15) x [44][45]<...>…”
Section: Discussionmentioning
confidence: 99%
“…Typical perturbation parameters are jitter, shimmer and harmonics-to-noise ratios in their different interpretations. This has been the traditional approach and is well documented in the works of different researchers [1][2] [3][4] [5]. The main objection to this methodology is that the original voice signal is contaminated by phonetic-acoustic information related to specific articulation features, and therefore perturbation parameters derived from this signal are influenced by articulation, making it difficult to grant new advances towards pathology classification.…”
Section: Introductionmentioning
confidence: 99%
“…To date, very few studies have evaluated the discriminative capabilities of the acoustic parameters. With the same database used in this study, Parsa evaluated the discriminative capabilities of several noise features 17 [17][18][19][20][21] indicate that an accurate screening can be carried out using a combination of several of the above-mentioned acoustic parameters, enabling each individual voice utterance to be quantified by a single set of one-dimensional parameters (similar to those enumerated above). Although the multidimensional studies reported a good efficiency in screening (obtaining accuracies up to 96%), 20,21 such analysis is not always easy to interpret from the perspective of a human evaluator and it is usually carried out by methods based on complex pattern recognition techniques.…”
Section: Introductionmentioning
confidence: 99%
“…Such parameters (jitter, shimmer, Harmonics to Noise Ratio (HNR), Normalized Noise Energy (NNE), Voice Turbulence Index (VTI), Glottal to Noise Excitation Ratio (GNE), Signal to Noise Ratio (SNR), Frequency Amplitude Tremor (FATR), and many others [1][2][3][4][5][6]) were developed to measure quality and ''degree of normality'' of voice registers from the sustained phonation of vowels. Using this acoustic material, previous studies [7][8][9] indicate that the detection of voice alterations can be carried out by means of the above-mentioned long-term averaged acoustic parameters, enabling each individual voice utterance to be quantified by a single vector. The main drawback of most of these parameters is that they relay on an accurate estimation of the fundamental frequency, a rather complicated task in presence of certain pathologies.…”
Section: Introductionmentioning
confidence: 99%